Перспективи розвитку інформаційно-діагностичних засобів управління та захисту медичного обладнання - Кривоносов, Валерій Єгорович; Піротті, Євген Леонідович; Азархов, О. Ю.; Коваль, Л. Г.; Паламарчук, М. В. ("ВМВ", 2018)
В роботі розглянуті перспективи розвитку інформаційно-діагностичних засобів управляння та захисту медичного обладнання. Розглянуті питання розробки інформаційно-діагностичних методів управління і захисту блоків медичного обладнання. Наведена математична модель попередження збитків.

Prospects of development of information-diagnostic means of management and protection of medical equipment are considered in this work. The issues of development of information-diagnostic methods of management and protection of blocks of medical equipment are considered. The mathematical model of damage prevention is presented. Modern diagnostic and therapeutic medical equipment (MO) are complex technical devices that contain electrical elements, mechanical units, electronic and microprocessor blocks, operating on low voltage and high voltage voltages, with a power of 30 kW and above. IO is installed, as a rule, in enclosed areas receiving power supply on separate lines and have independent nodes of relay protection of uninterruptible power supply units. The practice of using imported IM shows that it is very sensitive to the quality of electricity of Ukrainian 2-and 3-phase networks. The quality of electricity (PAYE) is not taken into account in the process of operating the medical equipment, although it is in the delivery of the MI. This results in operational failures and malfunctions caused by unpredictable changes in the network supply voltage parameters. Exit PYAE beyond the norm, established GOST. 13109-97 leads to the complication of finding and troubleshooting the malfunction and its elimination, as well as - to increase financial and time costs. To select and evaluate the effectiveness of the multi-level diagnostic management and protection system of the MO, the authors proposed a multi-level criterial assessment of the choice of the system of protection, in which the main criterion is the mathematical expectation of the set, which consists of the cost of the warnings.
Perspectives for development of informational and diagnostic means of management and protection of medical equipment
Keywords: болтове з`єднання; попередження збитків; мережі живлення; технічні пристрої; мікроконтролери; medical equipment; bolted connection; loss prevention; power supply